PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA. (Studi Kasus Pada Perusahaan Food and Beverage Tahun 2019-2020) - Firman Rizki Subakhtiar; Dwiyani Sudaryanti; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purposes of this research are to find out 1) The influence of environmental performance on financial performance, 2) The effect of environmental costs on financial performance, and 3) Company size on financial performance. This research uses purposive sampling method. The sample in this study were 29 food and beverage companies listed on the IDX in 2019-2020. The data analysis techniques used are multiple linear regression with descriptive analysis test, normality test, classical assumption test, coefficient of determination test, partial test and simultaneous test to determine the relationship between variables. By using the SPSS statistical tool, the results of this study indicate that 1) Environmental performance has an effect on financial performance, 2) Environmental costs have a negative and significant effect on financial performance, 3) Company size has an effect on financial performance. This research can contribute to legitimacy theory and stakeholder theory.  Keywords: Environmental Performance, Environmental Costs, Company Size, Financial Performance